On Split Exact Sequences and Projective Semimodules - Bhambri, S. K.; Dubey, Manish Kant (Sarajevo Journal of Mathematics, 2024)
In this paper the notion of split exact sequences of semimodules is introduced. We also study some results on projective semimodules that are analogous to module theory. 2000 Mathematics Subject Classification. 16Y60